Sex- and region-specific associations of skeletal muscle mass with metabolic dysfunction-associated fatty liver disease - Xiao, Pei; Liang, Pu; Gao, Panjun; Wu, Jinyi (Frontiers in Endocrinology, 2022)
Background & Aims: Metabolic dysfunction-associated fatty liver disease (MAFLD) is known to be the most common chronic liver disease worldwide, and accumulating evidence suggests that skeletal muscle might play an important role in metabolic health. However, the association between skeletal muscle and MAFLD is poorly understood so far. Therefore, we aimed to evaluate the associations of skeletal muscle with MAFLD and significant fibrosis. Methods: A cross-sectional analysis was conducted using data obtained from the 2017-2018 US National Health and Nutrition Examination Survey. The whole-body, appendicular, and trunk skeletal muscle mass index (SMI) were assessed by dual-energy x-ray absorptiometry. MAFLD and significant fibrosis were assessed by transient elastography. Survey-weight adjusted multivariable logistic regressions were used to determine the associations. The area under the receiver operating characteristic curve (AUC) and variable importance scores from random forest and logistic regression model were calculated to assess the predictive capability of variables and models. Results: Of the 2065 participants, those with appendicular SMI in the highest quartile were associated with a lower risk for MAFLD in both sexes (male, OR[95%CI]: 0.46 [0.25~0.84]; female, OR[95%CI]: 0.32 [0.13~0.82]), but with a significantly different scale of the associations between sexes (Pinteraction = 0.037). However, females with trunk SMI in the highest quartile had an increased risk of significant fibrosis (OR[95%CI]: 7.82 [1.86~32.77]). Trunk SMI and appendicular SMI ranked the third contributor to MAFLD in random forest and logistic regression models, respectively. Taking appendicular and trunk SMI into consideration, the AUCs for MAFLD were 0.890 and 0.866 in random forest and logistic regression models, respectively. Conclusions: The distribution of skeletal muscle mass differently affects MAFLD and significant fibrosis in the sex groups. Higher appendicular skeletal muscle mass was associated with a lower risk of MAFLD, while the risk of significant fibrosis in females was increased with the trunk skeletal muscle mass.